2017
DOI: 10.1007/s00894-017-3478-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic study of iron-based dye sensitizers for solar cells using DFT/TDDFT

Abstract: Ruthenium-based molecules have proven their efficiency as photosensitizers in dye-sensitized solar cells. However, due to the high cost and scarcity of this noble metal, in this work we investigated the effects of replacing the ruthenium in photosensitizers with iron because it is less expensive and more abundant. DFT and TD-DFT methods were used to explore the resulting systems. The B3LYP functional was employed to compute the ground-state geometries and the frontier molecular orbitals for four complexes of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…But due to the scarcity of these particular metals in earth's crust, the development of organic dyes or dyes with abundant metal ions for the DSSC studies are important. Iron (fourth abundant element in earth's crust) has very recently been used for DSSC with TiO 2 . Current studies also showed some applications of nickel, chromium, copper, and zinc metal ions (some other earth‐abundant metal ions) for DSSCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But due to the scarcity of these particular metals in earth's crust, the development of organic dyes or dyes with abundant metal ions for the DSSC studies are important. Iron (fourth abundant element in earth's crust) has very recently been used for DSSC with TiO 2 . Current studies also showed some applications of nickel, chromium, copper, and zinc metal ions (some other earth‐abundant metal ions) for DSSCs .…”
Section: Introductionmentioning
confidence: 99%
“…Iron (fourth abundant element in earth's crust) has very recently been used for DSSC with TiO 2 . [55][56][57] Current studies also showed some applications of nickel, chromium, copper, and zinc metal ions (some other earth-abundant metal ions) for DSSCs. [58][59][60][61][62][63][64][65] Nickel(II) polypyridyl complexes have also recently been used as a catalyst for hydrogen production from water.…”
Section: Introductionmentioning
confidence: 99%
“…The PCE provides a basis for the design of high-conversion-efficiency DSSCs and can be determined by theoretical methods using eq where FF refers to the fill factor, which was set at 0.68, and P inj denotes the power of the incident light ( P in = 100 mW cm –2 at AM 1.5). It is observed (Table ) that the PCE values of D1T, D1F, and D1P are 11.25, 12.13, and 13.50%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Molekular dye berbasis Ruthenium, Ru, merupakan salah satu dye yang paling efektif di DSSC sampai saat ini. Namun dikarenakan harga yang cukup mahal dan kelangkaan dari logam ini, banyak penelitian mengembangkan pengganti dari molekular dye berbasis Ruthenium dengan fokus di pigmen alami yang berasal dari alam sebagai alternatif penggantinya [12]. Beberapa pigmen organik alami yang ada pada tumbuhan dapat digunakan sebagai dye sensitizer di piranti DSSC adalah coumarin, merocyanine, cyanine, indoline, hemicyanine, triphenylamin, dialkylaniline, phenothiazine, tetrahydroquinoline, dan carbazole yang memiliki kemampuan mengkonversi energi matahari menjadi listrik dengan efisiensi sebesar 5% − 9% pada panel surya DSSC [13][14][15].…”
Section: Pendahuluanunclassified